Exploring the motivations and obstacles to using e-learning professional development kits in teachers' professional development (The International Journal of Educational Sciences and Arts, 2026)
Professional development for teachers is among the most important goals that educational institutions strive to achieve due to its positive impact on learning outcomes. Online professional learning communities (ELCs) are one of the modern methods for teacher professional development.Therefore, this study aimed to examine teachers' opinions regarding the motivations and obstacles to using ELCs in their professional development. The phenomenological approach was used in this study to analyze the opinions of six participating teachers in order to gain a deep understanding of the motivations and obstacles to using ELCs in their professional development.Semi-structured interviews were used to collect data. The study's findings revealed that there are motivations for using ELCs in teacher professional development related to three axes: speed, flexibility, and problem-solving.The study also found that there are obstacles to using ELCs in teacher professional development related to two axes: technical obstacles and a lack of incentives.The study recommends educating teachers about the benefits of ELCs and providing incentives for teachers participating in ELCs.
Keywords: Online Professional Learning Groups; Professional Development; Teachers